IMPLEMENTATION OF SOCIAL ENTREPRENEURSHIP IN IMPROVING CREATIVE ECONOMY AND INNOVATION OF MSMES - Kaniawati, Keni; Gumelar, Agil; Putra, Davor Ray; Maulana, M.Kevin; Fadloli, M.Rizqi; H, Denal Maulana.T. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Social entrepreneurship is a business that is built with the aim of addressing problems that exist in a community group, such as economic problems, public health, education, environment, sanitation and so on. By constantly innovating and experimenting using the latest technology, social enterprises are constantly working to fill the gaps in the lives around them. Not only that, businesses run for the good of the community will increase confidence in a local identity, and help develop local people's confidence in their ability to be financially independent. The creative economy sector absolutely must get attention, because this sector has an important role in the national economy. But efforts to develop the current and future keratif economic sector still face the problem that the determination of creative economy subsectors has not been accompanied by systemic preparation efforts, the presence of the creative economy as a form of creative-innovative ideas of the community and its economic benefits, has not been able to stimulate local governments, especially to respond immediately through arrangement and structuring and development of businesses and creative products that are able to provide added economic value and value to the economy. Benefits that can be directly felt by the community and diversification of culture and potential of a specific region.The purpose of this research is to address economic or social problems, especially the creative economy and innovation in MSME products in West Java. With descriptive research methods provide solutions for social entrepreneurship strategies and strategies that will be implemented in MSMEs in West Java. The results of the analysis stated that the implementation of social entrepreneurship is very significant in the development of the creative economy and product innovation of both goods and services in MSMEs in West Java.